Management of obstructive urolithiasis by tube cystostomy technique in male buffalo calves - MANGOTRA, VIKAS; SINGH, KULDIP; CHAUDHARY, R N; KUMAR, ASHOK; TAYAL, RISHI (The Indian Journal of Animal Sciences, 2016)
The study was conducted on 35 male buffalo calves suffering from obstructive urolithiasis. The common clinical signs recorded were anuria, dull anxious look, kicking at the ventral abdomen, persistent efforts for micturition, which may be accompanied by rectal prolapse and pulsating urethra with contraction and relaxation of preputial orifice in cases with intact urinary bladder whereas bilateral distension of abdomen with fluid thrill, sunken eyes and no effort for micturation in cases of ruptured urinary bladder. The heart rate and respiratory rate were mildly elevated. The haematological parameters showed no significant changes. There was a significant increase in blood urea nitrogen, serum creatinine and plasma potassium which returned to near normal level in 48 h post-operatively. The pH of urine changed from alkaline to slightly acidic during the course of treatment. Ultrasonography was very effective tool for examining the status of urinary system in affected animals. Tube cystostomy had a high success rate in treating cases of obstructive urolithiasis in buffalo calves.